MANAGEMENT OF GREEN PRAMUKA CITY APARTMENT DIRECTLY BY THE DEVELOPER WITHOUT INVOLVEMENT OF THE ASSOCIATION OF UNIT OWNERS AND RESIDENTS (PPPSRS) - Christopher Alexandro Lumban Gaol (Pena Cendekia Insani, 2025)
This study focuses on the dynamics of condominium ownership as a form of vertical housing in urban areas of Indonesia, which involves not only the ownership of private space but also rights and obligations over common areas. The issues that arise are closely related to legal, social, and governance aspects, particularly in the utilization and management of shared facilities, which often lead to conflicts among residents. The research method employed is a qualitative approach with normative-juridical and empirical analysis. Data were obtained through literature review, regulatory analysis, and in-depth interviews with condominium residents, managers, and other relevant stakeholders. The findings indicate that there remains a gap between the legal regulations governing condominium ownership and actual practices in the field. The main obstacles lie in weak supervision, low legal awareness among residents, and overlapping authorities between managers and unit owners. The implications of this research emphasize the importance of strengthening more operational regulations, enhancing managerial capacity, and providing legal education to the community in order to create harmonious and equitable condominium governance.